Administration of BDNF/ginsenosides combination enhanced synaptic development in human neural stem cell - Wang, Lina; Kisaalita, William S. (Journal of neuroscience methods, 2011)
Ginsenosides Rg1 and Rb1, major pharmacologically active ingredients from Ginseng, the root of Panax ginseng C.A. Meyer (Araliaceae), were applied in the differentiation media for human neural stem cells (hNSCs), together with brain-derived neurotrophic factor (BDNF), a commonly used compound for neural stem cell (NSC) differentiation. Cell locomotion and neurite extension were observed by time-lapse microscopy and analyzed by ImageJ software. The expression of synaptic formation was confirmed by immunostaining of synaptophysin (SYN) or/and the co-localization of synapsin I and microtubule associated protein-2 (MAP-2). Effects of cell density on neural differentiation were also examined. Results have shown that administration of BDNF/ginsenosides (Rg1 and Rb1) combination in differentiation medium promoted cell survival, enhanced neurite outgrowth and synaptic marker expression during differentiation. High cell density enhanced synaptic marker expression in BDNF/ginsenosides combination medium. In all, this study established a condition for hNSCs synaptic development in early differentiation, which is a crucial step in applying this cell line in neural network-based assay.